Sarcopenia in Patients With Spinal Metastasis: A Systematic Review and Meta-Analysis of Retrospective Cohort Studies - Tan, Haifeng; Gao, Xiaoyu; Li, Xiaoyu; Huang, Yunling; Cao, Qi; Wan, Teng (Frontiers in Oncology, 2022)
Abstract Background：Predictive models designed to estimate mortality in spinal metastasis patients are reported with limited accuracy. Many retrospective cohort studies show sarcopenia is associated with mortality in spinal metastasis, while a lack of higher level of evidence is existing. Introduction：As a risk factor leading to adverse events in many diseases, sarcopenia may have an impact on patients with spinal metastasis. We aimed to perform a systematic review and meta-analysis of available retrospective cohort studies where sarcopenia is used to assess outcomes in spinal metastasis patients. Methods: On October 7, 2021, we performed a search in PubMed, Embase, and the Cochrane Library. Effect estimates with 95% CI were combined by random effects model. Sensitivity analyses were performed to explore sources of heterogeneity and stability of results. Results: Of the 4196 papers screened, 10 population-based retrospective cohort studies were included, with a total of 1674 patients. Overall, sarcopenia was associated with higher overall mortality (OR, 1.60; 95% CI 1.35-1.90) and lower Overall survival (HR, 2.08; 95% CI 1.55-2.80). Conclusions: Sarcopenia is a robust indicator of mortality in spinal metastasis patients.